Testing of concrete abrasion resistance in hydraulic structures on the lower Sava river - Kryžanowski, Andrej (Strojniški vestnik, 2012)
The paper deals with the issues of resistance of concrete linings to long-term abrasion loading caused by waterborne particles, particularly for the proposed hydro power plants on the Sava river in Slovenia. The main purpose of the research work was to define the possibility of forecasting the process of concrete lining wear on the Sava river dam structures based on the standard procedures of abrasion resistance testing. Abrasion resistance of concrete has been researched in accordance with the standard ASTM C 1138 and Böhme (DIN 52108) methods. The research work was based on a comparison between laboratory results and measurements of abrasion resistance of concrete under natural conditions by performing test plots in the stilling basin of the Vrhovo HPP. Concrete composites with different mechanical properties have been analysed within the research programme. The analysis showed a qualitative similarity of the level of concrete abrasion between laboratory simulations and measurements in the field, as well as suitability of the ASTM C 1138 laboratory method for the assessment of abrasion resistance of concretes in the spillway of the HPP chain on the lower Sava river.
Keywords: abrazijska odpornost; beton; laboratorijski poskusi; obraba; poskusi v naravi